Effectiveness of Interactive Web Technology in Improving Students Arabic Language in the Higher Education of Islamic State Sumatera - Akla , Nopiana , Ani Susilawati , Sri Wahyuni (International Journal of Advanced Science and Technology, 2020)
This study aims to determine the effectiveness of interactive web technologies in improving students’ mastery of Arabic at the State Islamic University of Sumatra. The design of this study is quasi-experimental. The sample of this study were students who programed Arabic courses 2 at IAIN Metro and UIN Raden Intan Lampung, totaling 160 people. The sample was divided into 4 classes: 2 experimental classes and 2 control classes from IAIN Metro and UIN Raden Intan Lampung. Data collection techniques using Arabic language mastery test 2. Data analysis of this study was carried out using a t-test with the prerequisite test for normality test and homogeneity test. The results of the analysis using the SPSS 16 program are known to test the sig normality value of each experimental class and the control class that is 0.084, 0.067, 0.063, and 0.072 respectively, which means the sample comes from populations that are normally distributed. Furthermore, the homogeneity test results known the sig value 0.993 which means the population has a homogeneous variance. T-test results with the SPSS program obtained a sig (2-tailed) value of 0,000 so that it was concluded that interactive web technology was effective in increasing students’ Arabic Language mastery at the Sumatran Islamic Religious College.